Integrating Medicine and Pharmacology: The Burden of Heart Failure in Diabetes, Its Treatment Patterns and Consequences for Patient Quality of Life - Nadeem Akhtar Korai, Saim Sattar, Narindar Kumar, Anum Ashraf, Ain-Ul Momina, Mohammad Atiq Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim of the Study: This study aimed to investigate the burden of heart failure (HF) in patients with diabetes mellitus (DM), analyze treatment patterns integrating medicine and pharmacology, and assess the consequences for patient quality of life (QoL). The objective was to bridge clinical practice and pharmacological interventions, thereby highlighting both therapeutic success and existing gaps in management. Study Duration: The study was conducted over a 12-month period, from May 2022 to May 2023. Place of Study: Data collection and patient evaluation were undertaken at Watim Medical & Dental College, Rawalpindi, and Jinnah Hospital, Lahore, two tertiary care centers providing specialized cardiovascular and endocrine services. Methodology: A cross-sectional observational design was employed. A total of 450 patients with type 2 diabetes and diagnosed HF were included. Clinical parameters, comorbidities, pharmacological treatments, and QoL outcomes (assessed using the Kansas City Cardiomyopathy Questionnaire) were analyzed. Treatment regimens were categorized into diuretics, renin-angiotensin-aldosterone system (RAAS) inhibitors, beta-blockers, SGLT2 inhibitors, and combination therapies. Data were analyzed using descriptive and inferential statistics. Results: Patients with coexisting HF and DM demonstrated significantly impaired QoL scores compared to general HF cohorts. SGLT2 inhibitors and RAAS inhibitors were associated with improved symptom control and QoL indices, whereas those on diuretics alone had poorer outcomes. The mean URR (%) and Kt/V equivalents in dialysis-comparable pharmacological adequacy revealed superior outcomes in patients receiving combined pharmacological regimens. Conclusion: Heart failure in diabetes constitutes a double burden that severely impacts patients’ QoL. Integrated pharmacological approaches provide superior outcomes compared to monotherapy. The findings underscore the urgent need for multidisciplinary strategies linking internal medicine, pharmacology, and patient-centered care. Keywords: Heart failure, diabetes mellitus, pharmacological treatment, quality of life, SGLT2 inhibitors, RAAS inhibitors, integrated medicine